Development of Innovative Tools and Models for Vocational Education and Training in Central and Western Romania - Liviu Moldovan (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2009)
This paper presents an initiative developed by two partner universities from Romania and Norway entitled „Innovative Tools and models for Vocational Education and Training in Central and western Romania” (MoVE-IT) financed by SEE mechanism [1]. It has the priority to develop human resource through promotion of education and training, by means of distance learning. The objective, legal issues, outcome and results and envisaged impact of the project are presented.